Facile synthesis of CsPbBr3 perovskite for improved stability and luminescence behavior in an aquatic environment - Wei, Xianqi; Lu, Jiayi; Zhang, Silong; Tang, Jiashu; Wu, Shichao; Lv, Tengbo; Wang, Xiaoli (Frontiers in Chemistry, 2025)
CsPbBr3 (CPB) perovskite has demonstrated unique advantages as a photoelectric material. However, its stability and optoelectronic properties exhibit significantly susceptibility to environmental conditions during practical applications. Additionally, the synthesis of CPB often involves complex procedures and stringent requirements for the experimental environment, resulting in low yield. In this study, we employed an aqueous-phase synthesis method to incorporate strontium into CPB, aiming to enhance the long-term stability of the perovskite in aqueous solutions. And the introduction of strontium (Sr) is expected to improve the photoluminescent properties of the perovskite. The results demonstrate that the synthesized perovskite remains stable in aqueous solution for up to 264 h, with enhanced photoluminescence intensity and a blue shift attributed to the incorporation of strontium. This approach significantly increases the potential value of CPB perovskite for applications in optoelectronic materials and devices.